Corneal transplantation for keratoconus - Jonuscheit, Sven; Doughty, Michael J (Scandinavian Journal of Optometry and Visual Science, 2013)
This review discusses current techniques of corneal transplantation for moderate to advanced keratoconus. The aim of this article is to provide primary eye care practitioners with an overview of two current corneal transplantation modalities, namely penetrating and deep anterior lamellar keratoplasty. The main surgical techniques, the outcome of the procedures, common complications and the prognosis will be reviewed. Results from ongoing studies at a corneal transplant centre in Glasgow, Scotland will be discussed.